Dilemma of Reporting Incidental Findings in Newborn Screening Programs for SCID: Parents’ Perspective on Ataxia Telangiectasia - Blom, Maartje; Schoenaker, Michiel H. D.; Hulst, Myrthe; de Vries, Martine C.; Weemaes, Corry M. R.; Willemsen, Michèl A. A. P.; Henneman, Lidewij; van der Burg, Mirjam (Frontiers in Immunology, 2019)
Abstract Background: Ataxia Telangiectasia (A-T) is a severe DNA repair disorder that leads to a broad range of symptoms including neurodegeneration and a variable immunodeficiency. A-T is one of the incidental findings that accompanies newborn screening for severe combined immunodeficiency (SCID), leading to an early diagnosis of A-T at birth in a pre-symptomatic stage. While some countries embrace all incidental findings, the current policy in the Netherlands on reporting untreatable incidental findings is more conservative. We present parents’ perspectives and considerations on the various advantages versus disadvantages of early and late diagnosis of A-T. Methods: A questionnaire was developed and sent to 4000 parents of healthy newborns who participated in the Dutch SONNET-study (implementation pilot for newborn screening for SCID). The questionnaire consisted of open-ended and scale questions on advantages and disadvantages of early and late diagnosis of A-T. To address potential bias, demographic characteristics of the study sample were compared to a reference population. Results: A total of 664 of 4000 parents sent back the questionnaire (response rate 16.6%). The vast majority of parents (81.9%) favoured early diagnosis of A-T over late diagnosis. Main arguments were to avoid a long period of uncertainty prior to diagnosis and to ensure the most optimal clinical care and guidance from the onset of symptoms. Parents who favoured late diagnosis of A-T stated that early diagnosis would not lead to improved quality of life and preferred to enjoy the so-called ‘golden years’ with their child. The majority of parents (81.1%) stated that they would participate in newborn screening for A-T if a test was available. Conclusions: Reporting untreatable incidental findings remains a disputed topic worldwide. Although the current policy in the Netherlands is not to report untreatable incidental findings, unless the health advantage is clear, the majority of parents of healthy newborns are in favour of an early A-T diagnosis in the pre-symptomatic phase of the disorder. Our results as well as other studies that showed support for the screening of untreatable disorders may serve as valuable tools to inform policymakers in their considerations about NBS for untreatable disorders.